A novel bio‐based, flame retardant and latent imidazole compound—Its synthesis and uses as curing agent for epoxy resins. Issue 44 (1st September 2022) - Yang, Bo; Wei, Yi; Qiu, Yiping; Ramakrishna, Seeram; Liu, Yanbo
Abstract: Composite industry is constantly seeking multifunctional, high performance and environmentally friendly materials. Herein reported is a novel bio‐based, flame retardant and latent epoxy curing agent synthesized from wood vanillin, phosphate ester and imidazole. Experiment data from combustion test demonstrated that the cured epoxy resin with this new curing agent, designated as VAIP, rendered effective flame retardant property with limit of oxygen of 38.4%, UL‐94 V‐0 rating, total heat release of 48 MJm −2 and peak heat release rate of 435 KWm −2 . Thermal mechanical tests showed its significantly higher char yield of 35% at 800°C and thermal stability with the temperature of initial weight loss rate of above 350°C, compared to reference epoxy resins cured by conventional cyano‐imidazole (CEMI). This new phosphorus containing imidazole curing agent also demonstrated potential application in fiber‐reinforced composite by rendering comparable Tg, for both dry and hot‐wet conditions, as well as higher interlaminar and shear strengths, when compared with the reference composite. Dynamic rheological isothermal measurement of the epoxy resin viscosity further concluded that VAIP had significantly better latency of 580 min at 60°C and 14 days at room temperature, resulting in much longer pot life or shelf life for the formulated resins and their prepreg. Abstract :